Inside the Psyche of LGBTQ+ Community: A Pensive Voyage Through an Asian Graphic Novel - et. al., ARATHI P S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Over the past few years, the LGBTQ+ community has reached exceptional milestones, but yet, they need to achieve more to find and establish their place in this world. A similar aspect lies with Graphic novels that they need to find and establish their place in the vast field of literature, though they are recently being printed and produced in massive numbers around the world. There seems to be no perfect medium than the Graphic Novels to voice the mental agonies faced by the LGBTQ+ community and its people. With the combination of the LGBTQ+ community and the graphic novels, this paper aims to act as an intermediary to convey the trouble and pain the LGBTQ+ community has to undergo, to the reading public. The analysis is performed upon My Lesbian Experience with Loneliness (2017) authored by Kabi Nagata, a Graphic Novel that comes under the gradually developing Queer Graphic Novels. The central idea is to point out the importance of keeping the mental health of the LGBTQ+ people intact and providing social support like that provided to any other individual in this supposedly brilliant and advanced world. A much broader picture of social issues concerning the LGBTQ+ community is illustrated and discussed through the analysis of the Graphic Novel and thereby stating its importance among the humankind and economy. Through this, the paper provides a better understanding by dwelling deeper into the psyche of LGBTQ+ individual and their struggles.